Virtue Epistemology: Internalism and Externalism Justification - Akwaji, Agabi Gabriel; Nchua, Edward Augustine (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2018)
This research work titled, "Virtue Epistemology: Internalism and Externalism Justification” attempts to give a succinct analysis of the justification of our knowledge. It rigorously scrutinizes the sources of our knowledge claim. Whether the justificatory criteria to authenticate our knowledge claim are external or internal. It is discovered that the internalismexternalism (I-E) debate lies near the centre of the contemporary discussion about epistemology. The basic idea of internalism is that justification is solely determined by factors that are internal to a person. Externalists deny this, asserting that justification depends on additional factors that are external to a person. A significant aspect of the I-E debate involves setting out exactly what counts as internal to a person. One of the arguments for externalism is that if a process counts as cognitive when it is performed in the head, it should also count as cognitive when it is performed in the world. We sometimes perform actions in our heads that we usually perform in the world, so that the world leaks into the mind. Internalism has epistemological implications: if a process gives us an empirical discovery when it is performed in the world, it will also give us an empirical discovery when it is performed in the head. We explore the relation between internalism and externalism and contend that both are crucial and needed for justification. The work employed analytical, expository, and critical methods.